Problem Solving Skill Science on Junior High School for Different Academic - Arini Dwi Larasatining Retnowati; Suratno Suratno; Yushardi Yushardi (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
The rapid of education today requires empowerment skills to construct a science, one of the ways is adapting and training in a skill of problem-solving to face more advanced through learning and teaching materials. The purpose of this research is to know the difference skill of problem-solving based on learning science in junior high school in the different academic. Collecting data using rubric problem-solving skill given to students with academic distinction on April. The instrument of this research is a rubric problem-solving skill validated by the experts. The data were analysed with descriptive quantitative using Microsoft Exel. The result of data analysis of this research, there are some differences in problem-solving skills science of a junior high school of difference academic. A student who got the high score in academic tends to have better problem-solving skills.